Effect of Bovatec on grazing steer performance - Lomas, Lyle W. (Kansas State University. Agricultural Experiment Station, 2011)
Steers fed 100 mg or 200 mg of Bovatec per head daily while grazing bromegrass gained 16.4% and 23.9% faster, respectively, during 112 days of grazing than did controls.
Keywords: Beef; Steer Performance; Brome grass; Gain